1998
DOI: 10.1002/(sici)1096-8628(19980319)76:3<255::aid-ajmg10>3.3.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

X‐linked mental retardation with isolated growth hormone deficiency is mapped to Xq22–Xq27.2 in one family

Abstract: X-linked mental retardation (XLMR) includes distinct entities in which mental deficiency is either associated with specific abnormalities (syndromal) or not (nonsyndromal). We report on the clinical, neuropsychological, and laboratory findings and linkage analysis in one family with XLMR and isolated growth hormone deficiency (IGHD). Mental retardation was associated in 3 males and 5 females with short stature, microcephaly, and particular facial traits, i.e., high curved forehead, midface hypoplasia, and conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Given this finding, the Xq24 region is tentatively confirmed to be linked to height. In addition, three syndromes with short stature have been mapped to the Xq24 region (Table 4) (Cabezas et al 2000; Hamel et al 1996; Raynaud et al 1998; Vitale et al 2001). Further efforts are necessary to explore the Xq24 region's function in normal height variation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given this finding, the Xq24 region is tentatively confirmed to be linked to height. In addition, three syndromes with short stature have been mapped to the Xq24 region (Table 4) (Cabezas et al 2000; Hamel et al 1996; Raynaud et al 1998; Vitale et al 2001). Further efforts are necessary to explore the Xq24 region's function in normal height variation.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of syndromes with short stature provide unique models for study of human height development. Studies of these syndromes identified a list of causative genes and genomic regions (Cabezas et al 2000; Gelb et al 1996; Hamel et al 1996; Maheshwari et al 1998; Ramesar et al 1996; Raynaud et al 1998; Shiang et al 1994; Vitale et al 2001), which potentially may be related to normal height variation. Large‐scale whole genome linkage studies of height represent the latest effort of genetic dissection of this complex trait (Deng et al 2002; Hirschhorn et al 2001; Perola et al 2001; Wiltshire et al 2002; Xu et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Panhypopituitarism (PHP) (MIM 312000)10 and isolated growth hormone disorder (IGHD) (MIM 300123)11 localise to the same region (fig 5). Both have short stature but neither syndrome includes small testes.…”
Section: Discussionmentioning
confidence: 99%
“…Duplications including SOX3 have been associated with variable clinical phenotypes, including X-linked intellectual disability (ID), GHD, X-linked hypopituitarism (XH), SRY-negative 46,XX disorders of sex development (DSD) and neural tube defects (NTD) [27][28][29][30][31][32][33]. The severity of the phenotype is not dependent on the size of the duplication.…”
Section: Discussionmentioning
confidence: 99%